Effect of scattering on the transmission spectra of crystalline p-terphenil - Kovalenko, O.; Yunakova, O.; Makovetskyi, Y.; Yunakov, M. (Eskisehir Technical University, 2024)
Interest in studying the transmission spectra of crystalline p-terphenyl is due to the possibility of creating effective scintillators based on it. The samples of large volume or large area are used for this purpose. The transmission spectra of crystalline p-terphenyl samples with a thickness of 2 and 4 mm and a diameter of 18 mm are studied in this work.
Keywords: transmission spectrum; light scattering; organic crystals; scintillation materials